2020
DOI: 10.1127/anthranz/2020/1223
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of human growth – a systematic review on psychosocial factors influencing growth

Abstract: Background: This systematic review aimed at collecting, analyzing and summarizing scientific studies focusing on psychosocial factors that influence linear growth among humans. Methods: The online database "PubMed" was used in order to acquire suitable scientific studies. These studies were evaluated based on clearly defined criteria that determine whether a study was to be excluded or included in the literature review. In the end, a total sum of 36 studies remained, which were carefully analyzed and used to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Secular trends in height are commonly seen within countries, related to changing socio-economic status, nutrition, and health, and these can serve as public health indicators for interactions between growth and environment [3,4]. It has been demonstrated that social and psychological factors (such as socioeconomic status, parental education or emotional deprivation) are related to linear growth, and the effects of socio-economic crisis can increase low birthweight prevalence and can affect secular changes [27][28][29]. The effect of environmental factors may also explain differences in growth in children with CP from countries with difference socio-economic realities and healthcare systems, such as Germany and Argentina.…”
Section: Discussionmentioning
confidence: 99%
“…Secular trends in height are commonly seen within countries, related to changing socio-economic status, nutrition, and health, and these can serve as public health indicators for interactions between growth and environment [3,4]. It has been demonstrated that social and psychological factors (such as socioeconomic status, parental education or emotional deprivation) are related to linear growth, and the effects of socio-economic crisis can increase low birthweight prevalence and can affect secular changes [27][28][29]. The effect of environmental factors may also explain differences in growth in children with CP from countries with difference socio-economic realities and healthcare systems, such as Germany and Argentina.…”
Section: Discussionmentioning
confidence: 99%
“…However among humans who do not exist in strict dominance hierarchies but rather in a web of hierarchies, SES has been robustly associated with psychosocial stress profiles and disease outcomes (R. ; R. M. . For example, in a systematic review of 36 studies, Niere et al (2020) suggests that psychosocial factors (emotional and social) may influence linear growth in childhood depending on the environment. Among the studies they reviewed, they report that advantaged socioeconomic status, social positioning, and parental education are associated with more rapid growth tempo whereas disadvantaged SES, parental education and social mobility were associated with slower growth (Niere et al, 2020).…”
Section: Psychosocial Stress Hypothesesmentioning
confidence: 99%
“…For example, in a systematic review of 36 studies, Niere et al (2020) suggests that psychosocial factors (emotional and social) may influence linear growth in childhood depending on the environment. Among the studies they reviewed, they report that advantaged socioeconomic status, social positioning, and parental education are associated with more rapid growth tempo whereas disadvantaged SES, parental education and social mobility were associated with slower growth (Niere et al, 2020). Citing evidence from studies of emotional deprivation (Spencer, 2017), social isolation of migrant children (Özer & Scheffler, 2018) or childhood institutionalization (Kroupina et al, 2015), Niere et al (2020) andB.…”
Section: Psychosocial Stress Hypothesesmentioning
confidence: 99%
“…The findings of Maslow et al (2016) for the 9/11 WTC crisis add more evidence, in that women who only witnessed the events also had higher risk for LBW. Individual‐level studies document the association between birth outcomes and maternal psychological stress, ranging from chronic anxiety and depressive symptoms to acute stressors, determined by both pregnancy‐specific and general life event anxiety (reviewed in Niere et al, 2020; Varea et al, 2016). Potential pathways through which the experience of psychosocial stress by the mother may lead to negative perinatal outcomes have been proposed.…”
Section: How Stress Gets “Under the Skin”mentioning
confidence: 99%
“…These types of insecurities are often correlated, and this exacerbates the real and perceived psychosocial stress. It is well‐established that these stress factors have growth‐limiting impacts, as abundant research is available on SEPE gradients in height (Bogin, Scheffler, & Hermanussen, 2017; Niere et al, 2020).…”
Section: How Stress Gets “Under the Skin”mentioning
confidence: 99%